Women's Movement- An Analysis of Pre- Independent India - Mathew, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
The women's movement was founded on social reform like the outlawing of Sati, 1829 and enabling of the Widow Remarriage Act, 1856. The objective of the study was to provide an analysis of the Women's Movement in Pre- Independent India. The idea was to note the contribution of the Indian Women's Movement and the overall success of the Women's Movement in India. In the Indian context, the Women's Movement was divided into various phases according to Kiran Saxena 1994. The first phase was related to the movement by social reformers like PanditaRamabai. The second phase was carried forward by national leaders like Gandhi. So, our focus was on the first two phases. The role of Women's Organisations was commendable in improving the condition of women. Moreover, the research paper also explored the success of the Women's Movement in Pre -Independent India through legislative steps taken like the Devadasi Reform and the Brothel Act of the 1930s, political reform such the Universal Adult Suffrage of 1947. Besides, the Hindu Code Bill of 1955 also aimed at women's welfare. Throughout there were consistent efforts in society to remove the hurdles in women's education through reform.